The Effect of Diet and Stress Level in Women of Childbearing Age on the Menstrual Cycle at SMK Perguruan Rakyat 2 East Jakarta in 2023 - Sinta dewi, Ni Putu Savitri; Khairiyah, Rahayu (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT In addition to diet there are several factors that play a role in menstrual disorders, namely (1) psychological factors, such as life pressure, stress, anxiety, physical and psychological fatigue, (2) hormonal disorders, namely abnormalities in the hormones estrogen and progesterone and prostaglandins, (3) excess prolactin hormones, increasing these hormones will automatically reduce the hormones estrogen and progesterone hormones, (4) significant weight gain or loss,  (5) nutritional status (underweight if BMI 27.0) will affect the work of the system to improve, balance, and decrease hormones, (6) organic disorders such as inflammation, tumors, trauma and so on (Mamnu'ah, 2018). To determine whether there is an influence of diet stress levels in women of childbearing age on the menstrual cycle at SMK Perguruan Rakyat 2 in East Jakarta in 2023. The research method used is cumulative with data collection techniques, namely questionnaires or questionnaires. This study consisted of 3 variables, namely the first diet (free variable X1), the second stress level (free variable X2), and the third menstrual cycle (dependent variable). From the results of bivariate analysis using paried T Test the  effect of diet on women of childbearing age on the menstrual cycle at SMK Perguruan Rakyat 2 obtained p value (0.000) < alpha value (0.05). From the results of bivariate analysis using paried T Test, the effect of stress levels in women of childbearing age on the menstrual cycle obtained p.Value (0.000) < alpha value (0.05). The results showed that there was a significant influence between diet and stress levels in women of childbearing age on the menstrual cycle at SMK Perguruan Rakyat 2 in East Jakarta  ABSTRAK Selain pola makan ada beberapa faktor yang berperan dalam gangguan menstruasi yaitu (1) faktor psikologis, seperti adanya tekanan hidup, stres, kecemasan, kelelahan fisik maupun psikis, (2) gangguan hormonal yaitu ketidaknormalan hormon estrogen maupun progesteron serta prostaglandin, (3) hormon prolaktin berlebih, meningkatnya hormon ini otomatis akan menurunkan hormon estrogen dan hormon progesteron, (4) naiknya atau turunya berat badan secara signifikan, (5) status gizi (underweight jika IMT 27,0) akan berpengaruh pada kerja sistem peningkatan, keseimbangan, serta penurunan hormon, (6) kelainan organic seperti radang, tumor, trauma dan lain sebagainya (Mamnu’ah, 2018). Untuk mengetahui apakah ada pengaruh pola makan tingkat stres pada wanita usia subur terhadap siklus menstruasi di SMK Perguruan Rakyat 2 di Jakarta Timur Tahun 2023. Metode penelitian yang digunakan kunatitatif dengan teknik pengumpulan data yaitu kuesioner atau angket. Penelitian ini terdiri dari 3 variabel yaitu pertama pola makan (variabel bebas X1), kedua tingkat stres (variabel bebas X2), dan yang ketiga siklus menstruasi(variabel terikat). Dari hasil analisa bivariat menggunakan paried T Test pengaruh pola makan pada wanita usia subur terhadap siklus menstruasi di SMK Perguruan Rakyat 2 didapat nilai p valuenya (0,000) < nilai alpha (0,05)Dari hasil analisa bivariat menggunakan paried T Test pengaruh tingkat stres pada wanita usia subur terhadap siklus menstruasi didapat nilai p.Valuenya (0,000) < nilai alpha (0,05). Hasil penelitian menunjukkan bahwa terdapat pengaruh yang bermakna (significant) anatara pola makan dan tingkat stres pada wanita usia subur terhadap siklus menstruasi di SMK Perguruan Rakyat 2 di Jakarta Timur